A unique case of keratoconus with Cogan-Reese syndrome and secondary glaucoma - Lipi Chakrabarty (Indian Journal of Ophthalmology, 2017)
Keratoconus (KC), though one of the most common corneal degeneration, still continues to be a mystique regarding its pathogenesis, diagnosis, associations, and management; with newer discoveries and evolutions being reported. We report, what we believe to be another new association of KC- Cogan Reese syndrome with secondary glaucoma. A 32-year-old male, diagnosed as bilateral KC, presented for examination. Unilateral Cogan-Reese syndrome and associated secondary glaucoma was identified. These associations had been missed by previous ophthalmologists. The patient was managed with a rigid contact lens for KC and topical antiglaucoma agents for glaucoma. He was advised regular reviews and is under observation till date. We describe the first case known to us of a new association with KC. This case not only highlights the ophthalmologist's need to look for multiple entities linked to KC; but may also pave way for future insights regarding pathogenesis and genetics of these associated diseases.